Gendered Islamophobia : my journey with a scar(f) - Mazigh, Monia (Mawenzi House, 2023)
"This passionate book describes the author's struggles as a hijab-wearing Muslim woman, who was born and raised in a Muslim country (Tunisia) but has spent most of her adult years in Quebec, Canada as an immigrant. Mazigh describes her multiple identities and her multiple struggles against Islamophobia as it applies to women, who consistently get stereotyped as silent and dominated by their men."--